Evaluating Liquefaction Phenomenon Of Silty Sand Using Piezocone Penetration Test (CPTu) - Albert Johan; Paulus Pramono Rahardjo; Budijanto Widjaja (Kadiri University, 2022)
Most investigations into liquefaction have focused on clean sandy soils, with time, evidence has grown that liquefaction is often associated with silty sand material. Sibalaya Village, which suffered the greatest damage from the Palu-Donggala earthquake, is dominated by silty sand material. Related to this issue, an experimental study is conducted in the laboratory to understand the behavior of excess pore pressure and the strength of the saturated silty sand under dynamic loading. The experimental study uses several sets of testing apparatus such as a shake table, chamber, and CPTu. The shake table provides a dynamic load for the soil sample. The chamber allows the field environment to be duplicated in the laboratory. The CPTu measures excess pore pressure and strength of the soil sample. The test results show that liquefaction can occur in silty sand material. However, the fine-grain particles cannot generate the overall pore water pressure in which the pore water pressure ratio can only reach 93% of the initial effective vertical stress. Liquefaction also generates increased pore water pressure and a decrease in soil strength. The increase of dynamic load will result in a shorter liquefaction starting time, and fine content strongly influences the pore water pressure behavior, especially on the rate of pore water pressure dissipation after liquefaction occurs. Therefore, based on this research, it is known that silty sand material can experience liquefaction and can have a longer liquefaction period due to its lower permeability.